A Prospective, Non-randomized Feasibility and Preliminary Efficacy Study of a Telemedicine-Enabled Co-management Intervention for Adults With Type 2 Diabetes and Moderate Anxiety and/or Depression. Issue 2 (April 2021) - Magee, Michelle F.; Kaltman, Stacey I.; Mete, Mihriye; Nassar, Carine M.
Purpose: The primary aim of this pilot study was to examine the feasibility of codelivering a mental health intervention with an evidence-based type 2 diabetes (T2DM) boot camp care management program. The preliminary impact of participation on symptom scores for depression and anxiety and A1C was also examined. Methods: This was a 12-week, non-randomized pilot intervention conducted with a convenience sample of adults with uncontrolled T2DM and moderate depression and/or anxiety at an urban teaching hospital. Co-management intervention delivery was via in-person and telehealth visits. Participants were assessed at baseline and 90 days. Results: Participants (n = 18) were African American, majority female (83%), and age 50.7 ± 13.4 years. Significant improvements in mental health outcomes were demonstrated, as measured by a reduction in Patient Health Questionnaire − 9 scores of 2.4 ± 2.9 ( P = .01) and in Generalized Anxiety Disorder − 7 scores of 2.3 ± 1.9 ( P = .001). The pre-post intervention mean A1C improved by 3.4 ± 2.1 units from 12% ± 1.4% to 8.5% ± 1.7% ( P < .001). Conclusion: The data generated in this pilot support the feasibility of delivering a diabetes and mental health co-management intervention using a combination of in-person and telemedicine visits to engage adults with T2DM and coexisting moderate depression and/or anxiety. Further research is warranted.